Sero-prevalence of Human Cytomegalovirus among blood donors in Lahore, Pakistan - Chahat Batool Rizvi; Ali Raza; Maria Fareed Siddiqui; Rabail Alam (Advancements in Life Sciences, 2015)
Background: Transfusion-transmitted cytomegalovirus (TT-CMV) infection can cause severe illness and even death among immunocompromised patients; therefore, the spread of CMV through blood products should be prevented. To our knowledge, no study has been carried out in Pakistan to determine the seroprevalence of CMV in general population as well as among blood donors. The goal of this study was to determine CMV seropositivity among blood donors at the blood bank of INMOL Hospital, Lahore, Pakistan. Methods: A sero-epidemiological cross-sectional study was conducted. Sera from 91 blood donors were screened for CMV specific IgG antibodies by enzyme-linked immunosorbent assay (ELISA) based kit. Results: The CMV-specific IgG antibodies were detected in 89 blood donors, which gave seroprevalence rate of 97.8%. The statistical analysis of results was done using pearson chi-square test and appeared non-significant with values 0.625 and 0.705 for different age groups and blood groups of donors. Conclusion: Because of high seroprevalence in this study area, an adequate supply of CMV seronegative blood is difficult to maintain. Therefore, we propose that the future strategies for the prevention of post-transfusion CMV infection in recipients should include the transfusion of leukoreduced blood products. Further a prospective study with much greater population can be done to identify major causative risk factors for such highest prevalence rate.